Natural origin hydroxyapatite scaffold as potential bone tissue engineering substitute. Issue 16 (December 2016) - Mondal, Sudip; Pal, Umapada; Dey, Apurba
Abstract: Fish scales derived natural hydroxyapatite (FS-HAp) scaffolds were prepared through solvent casting technique, which could mimic the structure of cortical and cancellous bone tissues of body system. The hydroxyapatite (HAp) biomaterial was synthesized by thermal decomposition of chemically treated fish scales. Fabricated scaffolds were characterized through morphological analysis, volumetric shrinkage, mechanical tests, and in vitro, in vivo biological studies. The projected scaffolds successfully mimic the cancellous/cortical bone system in terms of structure, porosity, mechanical strength, and exhibit excellent bioactive behavior. The FS-HAp scaffolds manifest good mechanical behaviors with Vickers Hardness (HV) of 0.78 GPa, 0.52 GPa compressive stress, 190 MPa tensile stress and 35% porosity on sintering at 1200 °C. In vitro and in vivo studies suggest these nontoxic HAp scaffolds graft with osteoconductive support, facilitating new cell growth on the developed scaffold surface. The graded grafts have a great potential for application as traumatized tissue augmentation substitute, and ideal for load-bearing bone applications.